2021
DOI: 10.3389/fpsyg.2021.735755
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-Control and Internet Addiction Among Students: A Meta-Analysis

Abstract: As past studies of self-control and Internet addiction showed mixed results, this meta-analysis of 83 primary studies with 80,681 participants determined whether (a) these students with less self-control had greater Internet addiction, and (b) age, culture, gender, Internet addiction measures, or year moderated these relations. We used a random-effects meta-analysis of Pearson product-moment coefficients r with Fisher’s z-transformation and tested for moderation with the homogeneity tests. The results showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 95 publications
2
33
0
3
Order By: Relevance
“…On the other hand, students who have low scores of poor self-regulation also have a low level of internet addiction. This result is consistent with the previous study Li et al (2021). found that students with less self-regulation had greater internet addiction.…”
supporting
confidence: 94%
“…On the other hand, students who have low scores of poor self-regulation also have a low level of internet addiction. This result is consistent with the previous study Li et al (2021). found that students with less self-regulation had greater internet addiction.…”
supporting
confidence: 94%
“…There are indications from previous research that this could happen as a result of the students' SM addiction, which disrupts their time management skills (see Li et al, 2021) and lowers their academic achievement (Azizi, 2019) among other consequences. However, this study does not have any evidence to support that the lower academic performance of some of the students as well as the relatively longer time spent on SM is related to SM addiction or time management issues.…”
Section: Time On Social Media and Academicmentioning
confidence: 99%
“…Some studies have revealed that self-control-related factors (e.g., impulse control, self-regulation) are negatively related to gaming use [ 19 , 40 ]. Other studies have also demonstrated that self-control accounted for an indirect role between culture [ 41 ] or parental behavior and adolescents’ Internet addiction [ 33 ].…”
Section: Pathological Gaming and Adolescents’ Mental Healthmentioning
confidence: 99%